Quadrature Phase Shift Keying (QPSK) Modulator Design using Multi-Port Network in Multilayer Microstrip-Slot Technology for Wireless Communication Applications - Seman, Norhudah; Mohamed Ghazali, Siti Nor Ain (Společnost pro radioelektronické inženýrství, 2015)
The design of the quadrature phase shift keying (QPSK) modulator by using a multi-port network is proposed in this article for the use in wireless communication applications. The multi-port network is in the form of multilayer microstrip-slot technology. This multi-port network is composed of three 3-dB rectangular-shaped directional couplers with virtual stubs and an equal power division divider with in-phase characteristic. The design is performed by applying a full-wave electromagnetic simulation software, CST Microwave Studio (CST MWS). Keysight’s Advanced Design System (ADS) is applied in analyzing and evaluating the QPSK constellation of the proposed modulator. This comparatively small size of proposed design has been fabricated, and its wideband performance of 2 to 6 GHz is verified.
Keywords: Coupler; modulator; multi-port; power divider; QPSK; wireless